Refinement of Active and Passive Membrane Properties of Layer V Pyramidal Neurons in Rat Primary Motor Cortex During Postnatal Development - Perez-García, Patricia; Pardillo-Díaz, Ricardo; Geribaldi-Doldán, Noelia; Gómez-Oliva, Ricardo; Domínguez-García, Samuel; Castro, Carmen; Nunez-Abades, Pedro; Carrascal, Livia (Frontiers in Molecular Neuroscience, 2021)
Achieving the distinctive complex behaviors of adult mammals requires the development of a great variety of specialized neural circuits. Although the development of these circuits begins during the embryonic stage, they remain immature at birth, requiring a postnatal maturation process to achieve these complex tasks. Understanding how the neuronal membrane properties and circuits change during development is the first step to understand their transition into efficient ones. Thus, using whole cell patch clamp recordings, we have studied the changes in the electrophysiological properties of layer V pyramidal neurons of the rat primary motor cortex during postnatal development. Among all the parameters studied, only the voltage threshold was established at birth and, although some of the changes occurred mainly during the second postnatal week, other properties such as membrane potential, capacitance, duration of the post-hyperpolarization phase or the maximum firing rate were not defined until the beginning of adulthood. Those modifications lead to a decrease in neuronal excitability and to an increase in the working range in young adult neurons, allowing more sensitive and accurate responses. This maturation process, that involves an increase in neuronal size and changes in ionic conductances, seems to be influenced by the neuronal type and by the task that neurons perform as inferred from the comparison with other pyramidal and motor neuron populations.